ANALISIS PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO DAN CORPORATE SOCIAL RESPOSIBILITY TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KOMSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Muyassaroh muyassaroh (Accounting Department UNUSIA, 2023)
The company's going concern is supported by the availability of capital for the company. One way for a company to obtain a source of funds is by selling shares to the public in the capital market, however, investors do not simply buy and sell shares. Investors making investments must consider several aspects to minimize the risk of investing in stocks. One of them is by analyzing the company's financial statements that will affect stock returns. These ratios are return on assets to find out if the company gets a profit from its assets, Debt to equity to find out how much the company is financed by debt, Disclosure of Corporate Social Responsibility broadly will cause the company to have a good image in the view of stakeholders. The population of this study are manufacturing companies in the consumer goods industry sector listed on the IDX for the 2016-2020 period, the research sample was taken using a purposive sample method, after being determined according to the criteria, 135 companies were taken as samples. data collection techniques using secondary data, the data collected is analyzed with the Classical Assumption Test and hypothesis testing on SPSS. The results of this study indicate that return on assets, debt to equity and corporate social responsibility affect stock returns in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Based on the simultaneous significance test with the F test, the value obtained is significance of 0.00. Because the value is smaller than 0.05. The advice that can be given is to decide to invest in stock investments, investors should assess the company's performance through annual reports, especially on return on assets, debt to equity and corporate social responsibility because simultaneously it is very influential on stock returns. it is evident from the results of the R-Square of this study of 65.8%.